Giant axonal neuropathy: normal protein composition of neurofilaments. Issue 6 (June 1983) - Ionasescu, V; Searby, C; Rubenstein, P; Sandra, A; Cancilla, P; Robillard, J
Abstract : A 14-year-old boy had progressive weakness and ataxia since two years of age with tightly curled hair, facial diplegia, distal weakness and hypaesthesia, cerebellar syndrome and normal intelligence. He also had distal renal tubular acidosis manifested by metabolic acidosis. Sural nerve ultrastructure showed numerous giant axons packed with neurofilaments. The neurofilament major proteins of 68 000, 160 000 and 210 000 daltons found in normal sural nerve were also present in the diseased nerve indicating that the protein composition of neurofilaments which accumulates in this disorder has not been appreciably altered. The amount of 68 000 dalton neurofilament protein was two times higher in giant axonal neuropathy nerve than in the control nerve. Our results suggest that the neurofibrillary pathology in giant axonal neuropathy is due to a build-up of normal neurofilaments.